2003
DOI: 10.1038/sj.bjc.6600823
|View full text |Cite
|
Sign up to set email alerts
|

Peptide receptor radiotherapy: a new option for the management of aggressive fibromatosis on behalf of the Italian Sarcoma Group

Abstract: The management of aggressive fibromatosis (AF) is problematic, and few options are available to patients unsuitable for surgery and resistant to external-beam radiation therapy (EBRT). We report on two patients with fast-growing recurrences of AF resistant to EBRT who obtained protracted clinical benefits with 90 Y-DOTATOC. 90 Y-DOTATOC should be further investigated in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…There are data suggesting that some tumors have somatostatin receptor subtype 2 and may respond to treatment with a yttrium-90-radiolabeled somatostatin analog. 29 …”
Section: Resultsmentioning
confidence: 97%
“…There are data suggesting that some tumors have somatostatin receptor subtype 2 and may respond to treatment with a yttrium-90-radiolabeled somatostatin analog. 29 …”
Section: Resultsmentioning
confidence: 97%
“…In our present series, nine of 80 samples were positive for somatostatin. The benefit of treatment with peptide receptor radiotherapy using a somatostatin analogue, as proposed by De Pas and colleagues, 25 remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies analyzed somatostatin receptor expression in desmoid-type fibromatosis. De Pas et al [46] found positive reactions in two out of ten patients. Leithner et al [19] described nine positive samples out of 80.…”
Section: Somatostatinmentioning
confidence: 97%
“…Leithner et al [19] described nine positive samples out of 80. It is unclear whether therapy of desmoid tumors with peptide receptor radiotherapy using a somatostatin analogue as proposed by De Pas et al [46] is advantagsous.…”
Section: Somatostatinmentioning
confidence: 99%